Nonparametric IV Estimation of Local Average Treatment Effects with Covariates - Markus Frölich (Institute for the Study of Labor (IZA), 2002)
In this paper nonparametric instrumental variable estimation of local average treatment effects (LATE) is extended to incorporate confounding covariates. Estimation of local average treatment effects is appealing since their identification relies on much weaker assumptions than the identification of average treatment effects in other nonparametric instrumental variable models. Including covariates in the estimation of LATE is necessary when the instrumental variable itself is endogenous (e.g. when the instrument is self-selected). However, all previous approaches to handle covariates in the estimation of LATE rely on parametric or semiparametric methods. In this paper, a nonparametric estimator for the estimation of LATE with covariates is suggested that is root-n asymptotically normal and efficient.
Keywords: C13; C14; 330; instrumental variables; LATE; evaluation; treatment effect; matching; unobserved heterogeneity; Statistische Verteilung; Nichtparametrisches Verfahren; Instrumentalvariablen-Schätzmethode; Theorie